Criminal Law Analysis of Genocide as a Violation of Human Rights in Indonesia - Ismail, Andi Muh; Putera, Airlangga; Jannah, Miftahul (HORIZON PUBLIC LEGAL STUDIES, 2025)
The aim of this research is to understand and analyze legal regulations relating to genocide as a violation of human rights in Indonesia, both in Article 7 a and Article 8 of Law No. 26 of 2000 concerning Human Rights Courts, the old Criminal Code Regarding Genocide and Article 598 in Law No. 1 of 2023 concerning the Criminal Code which relates to genocide regulations. This study uses a normative research type (normative law research) or doctrinal legal research, namely legal research that uses legal material sources or is library research, a study of legal materials. The results of this study indicate that, First, the legal regulations relating to genocide as a violation of human rights in Indonesia, both in Article 7a and Article 8, have a definition of the crime of genocide. However, this article has advantages and disadvantages in interpreting and determining the crime of genocide. Second, actions that fall into the category of genocide in the old Criminal Code are often categorized as general crimes such as premeditated murder, serious abuse, or crimes against humanity. And third, the perpetrators are often only charged with general articles with lighter penalties than if there were special articles for genocide. So this will make the crime of genocide potentially committed by a group of people and result in loss of life throughout Indonesia in the future. Finally, Law No. 1 of 2023 includes genocide crime regulations in Article 598 which specifically regulates the crime of genocide. The suggestions from this study indicate the need for national regulatory officials, especially Article 7a and Article 8 of the Law on Human Rights Courts and Article 598 concerning genocide, to explain more clearly the crime of genocide, both in terms of definition, categorization of the crime of genocide and protection of victims.